2002
DOI: 10.1055/s-2002-31987
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Development of Gastric Ulcer after Percutaneous Endoscopic Gastrostomy

Abstract: The occurrence of gastric ulcer after PEG placement was attributable to the shape of the PEG tube within the intragastric space, and not to the use of H 2 -blockers, suggesting that appropriate placement of the PEG tube is an important factor in preventing gastric ulcer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 3 publications
0
23
0
Order By: Relevance
“…Forty-three patients were African American, 22 Caucasian and 2 Hispanic. Eighteen patients had life threatening conditions like colon cancer (2), lung cancer with metastasis (2), lung cancer without metastasis (2), prostate cancer (5), pituitary tumor (1), head and neck cancer (5), and esophageal cancer (1). Other co-morbid conditions in our patients were stroke in 12 patients, peptic ulcer disease in 5 patients, dementia in 2 patients, and Huntington's disease in 1 patient.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Forty-three patients were African American, 22 Caucasian and 2 Hispanic. Eighteen patients had life threatening conditions like colon cancer (2), lung cancer with metastasis (2), lung cancer without metastasis (2), prostate cancer (5), pituitary tumor (1), head and neck cancer (5), and esophageal cancer (1). Other co-morbid conditions in our patients were stroke in 12 patients, peptic ulcer disease in 5 patients, dementia in 2 patients, and Huntington's disease in 1 patient.…”
Section: Resultsmentioning
confidence: 99%
“…However, we believe that even if patients were taking proton pump inhibitors or H2-receptor blockers post PEG tube FOBT would be positive since bleeding is known to occur after PEG tube placement in the first few hours to days likely caused by puncture of mucosal or abdominal wall vessel [15][16][17][18] which would not be affected by proton pump inhibitor treatment. Even if patients were on H2-receptor blocker prior to PEG tube placement, the mechanism of gastric ulcer formation that may cause positive FOBT is mechanical injury of mucosa from PEG tube [5,19] rather than acid injury and conceivably H2-receptor blocker should therefore not affect the outcome of the FOBT. Occasionally in other studies, a screening FOBT is ordered inappropriately as for patients with life-limiting comorbidities [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemorrhaging resulting from ulcers is not caused by the procedure itself but by direct trauma from the replacement device. 20,21 We experienced 4 cases of hemorrhage after replacement. It is important to note that anticoagulation or antiplatelet agents were being administered in all 4 cases, and that administration of these agents is a risk factor of replacement-related hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Explanations have been published regarding the mechanism underlying the development of gastric ulcer after balloon gastrostomy tube placement. Kanie et al (8) reported that a PEG tube with a long protruding tip was associated with a significantly higher frequency of post-PEG gastric ulcer due to contact injury to the gastric mucosa caused by the tip of the tube. In our case, the gastric ulcer was observed on the posterior wall of the gastric angle, where the tip of the balloon tube came into contact with the mucosa.…”
mentioning
confidence: 99%